As festas populares e a qualidade de vida dos moradores de São Luiz do Paraitinga - Rosa, Leonardo Xavier da [UNESP]; Salgado, Andreia Maria Pedro [UNESP]; Delamaro, Maurício César [UNESP]; Coelho, Eduardo de Oliveira; Campos, Arminda Eugenia Marques [UNESP]; Pazello, Igor Sinhorini [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
It's a paper that investigates the influence of popular festivals in the quality of life of residents of the São Luiz do Paraitinga city . Nowadays, society lives for work, hoping to obtain better living conditions for much-needed activities and leisure facilities that provide well-being and quality of life. The investigation of quality of life was based on the WHOQOL -BREF instrument and happened in Divine Festival , which takes place in May. 200 residents of the city were interviewed. The analyzed data indicate a strong identification of the population with the party analyzed , generating sense of well being , positively affecting the quality of life of the participating individuals .Keywords: Quality of Life, popular festivals, behavior.

Trata-se de um artigo que investiga a influência das festas populares na qualidade de vida dos moradores da cidade de São Luiz do Paraitinga. Atualmente, a sociedade vive para o trabalho, na expectativa de obter melhores condições de vida, para tanto necessita de atividades e espaços de lazer que propiciem bem estar e qualidade de vida. A investigação da qualidade de vida teve como base o instrumento WHOQOL-bref e aconteceu na Festa do Divino, que ocorre no mês de maio. Foram entrevistados 200 moradores da cidade. Os dados analisados indicam uma forte identificação da população com a festa analisada, gerando sensação de bem estar, afetando positivamente a qualidade de vida dos individuos participantes.
Keywords: Quality of life; Popular festival; Behavior; Qualidade de vida; Festas populares; Comportamento